(untitled) (UNIZIK Journal of Educational Management and Policy, 2025)
The study investigated time management and task delegation as predictors of principals’ administrative effectiveness in public secondary schools in Anambra State. Two research questions guided the study, and two null hypotheses were tested at 0.05 level of significance. The study adopted correlational research design. The population comprised all the 267 principals in the 267 public secondary schools in Anambra State. Due to the manageable size of the population, census sampling technique was employed. Two researcher-structured questionnaires titled "Principals’ Time Management and Task Delegation Strategies Questionnaire (PTMTDSQ) and Principals’ Administrative Effectiveness Questionnaire (PAEQ)" were used for data collection, after the face and content validation were determined. Cronbach Alpha was used to compute the collected data gotten through pilot test. PTMTDSQ yielded reliability coefficients of 0.98 and 0.80 for clusters A and B were, respectively, while PAEQ yielded reliability coefficient of 0.88. The researcher administered copies of the questionnaires directly on the respondents with the help of five research assistants. Simple linear regression analysis (R) was used to answer the research questions, while R was used to determine the extent of the prediction between the independent variables (Principals’ time management and task delegation Strategies) and the dependent variable (principals’ administrative effectiveness) in the study. Findings, among others revealed that time management, and delegation of tasks significantly predict principals’ administrative effectiveness in public secondary schools in Anambra State. This implies that principals who actively adopt time management and tasks delegation are more likely to maintain high levels of administrative effectiveness in public secondary schools in Anambra State. The study recommends that the Anambra State Ministry of Education should encourage principals to adopt effective time management strategies since this has been shown to enhance their administrative effectiveness and improve the smooth running of school activities.